1983
DOI: 10.1073/pnas.80.11.3153
|View full text |Cite
|
Sign up to set email alerts
|

Hemolytic activity of influenza virus hemagglutinin glycoproteins activated in mildly acidic environments.

Abstract: Hemagglutinin (HA) glycoproteins isolated from influenza virus caused hemolysis and liposome lysis at pH < 6.0. The pH dependence was similar to that of the parent virus. Hemagglutination and hemolysis titers of HA were comparable with those of virus. The time course of hemolysis by HA was somewhat different from that by virus. HA did not cause fusion of erythrocytes in acidic media, in contrast to virus. Both HA and virus, previously incubated at pH < 6.0, lost their low-pH-induced hemolytic activity. Isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
99
0
1

Year Published

1984
1984
2003
2003

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 142 publications
(111 citation statements)
references
References 17 publications
11
99
0
1
Order By: Relevance
“…4, trypsinization of haemagglutinin-containing autoliposomes (as in the experiments of Skehel et al, 1982) at pH 7.0 caused no change in HA1 or HA2, but at acid pH the HA1 subunit was markedly affected. As was also found by Skehel et al (1982) and Sato et al (1983), this protein disintegrated to give a product with a mol. wt.…”
Section: Influence Of Norakin On the Sensitivity To Trypsin At Acid Pmentioning
confidence: 76%
See 4 more Smart Citations
“…4, trypsinization of haemagglutinin-containing autoliposomes (as in the experiments of Skehel et al, 1982) at pH 7.0 caused no change in HA1 or HA2, but at acid pH the HA1 subunit was markedly affected. As was also found by Skehel et al (1982) and Sato et al (1983), this protein disintegrated to give a product with a mol. wt.…”
Section: Influence Of Norakin On the Sensitivity To Trypsin At Acid Pmentioning
confidence: 76%
“…The data in the literature suggest that, to induce fusion (red blood cell lysis) the influenza virus haemagglutinin must undergo certain conformational changes which take place only at acid pH (Skehel et al, 1982;Sato et al, 1983;Daniels et al, 1983). The experiments with the haemagglutinin of influenza virus performed by Skehel et al (1982) and Sato et al (1983) demonstrated that these changes result in haemagglutinin aggregation which can be revealed by centrifugation in sucrose gradients and by electron microscopy.…”
Section: Influence Of Norakin On the Aggregation Of Fpv Haemagglutinimentioning
confidence: 99%
See 3 more Smart Citations